1988
DOI: 10.1007/bf01411499
|View full text |Cite
|
Sign up to set email alerts
|

New block copolymers V. Synthesis, characterization and morphological studies of poly(pentamethylene terephthalate)-b-(acrylonitrile butadiene rubber)

Abstract: A block copolymer was prepared by low temperature polycondensation between (acid chloride)-terminated poly(pentamethylene terephthalate) as the hard block, and amine-terminated acrylonitrile-butadiene rubber, as the soft block. The polymer was characterized by nitrogen analysis, IR and NMR spectroscopy. The polymer showed two glass transition temperatures (Tg) and exhibited two-phase morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…[4][5][6] Many groups have shown that adding compatibilizers to polymer blends reduces the size of the dispersed phase significantly (which is crucial for many properties) and reduces coalescence. 3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] By far, the most common method to compatibilize polymer blends is reactive compatibilization. 4,6 Reactive compatibilization uses complementary functional groups on the respective polymers to reduce the interfacial tension and suppress coalescence, resulting in stable morphologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Many groups have shown that adding compatibilizers to polymer blends reduces the size of the dispersed phase significantly (which is crucial for many properties) and reduces coalescence. 3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] By far, the most common method to compatibilize polymer blends is reactive compatibilization. 4,6 Reactive compatibilization uses complementary functional groups on the respective polymers to reduce the interfacial tension and suppress coalescence, resulting in stable morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome coalescence and improve phase stability, compatibilization is used . Many groups have shown that adding compatibilizers to polymer blends reduces the size of the dispersed phase significantly (which is crucial for many properties) and reduces coalescence . By far, the most common method to compatibilize polymer blends is reactive compatibilization …”
Section: Introductionmentioning
confidence: 99%
“…While not all of the studies were done for the purpose of barrier materials, these studies suggest opportunities to use the barrier properties of AN in the form of a copolymer, provided sufficient AN is incorporated. Besides statistical copolymerization, block copolymers containing AN have been made, which provides another route to incorporating PAN's barrier properties . The ability to polymerize AN by radical polymerization techniques, particularly by reversible activation/de‐activation polymerization (RADP) techniques such as reversible addition fragmentation transfer (RAFT), atom transfer radical polymerization (ATRP), and nitroxide mediated polymerization (NMP), makes the subsequent polymer interesting for barrier materials as the microstructure can be tuned in many possible ways due to the possibility of forming block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides statistical copolymerization, block copolymers containing AN have been made, which provides another route to incorporating PAN's barrier properties. [13][14][15][16][17][18][19][20][21][22][23][24][25] The ability to polymerize AN by radical polymerization techniques, particularly by reversible activation/ de-activation polymerization (RADP) techniques such as reversible addition fragmentation transfer (RAFT), atom transfer radical polymerization (ATRP), and nitroxide mediated polymerization (NMP), makes the subsequent polymer interesting for barrier materials as the microstructure can be tuned in many possible ways due to the possibility of forming block copolymers. Additionally, properties can be further combined into the AN containing (co)polymers by blending with other polymers.…”
Section: Introductionmentioning
confidence: 99%